IMPLEMENTASI NILAI-NILAI KARAKTER CINTA TANAH AIR PADA SISWA DI MI ROUDLOTUN NASYI’IN - Anggita Windi Saputri; Muhammad Sulistiono; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
The application of the character values of patriotism to students is very important to implement, with the waning of character values of patriotism that erode the spirit of the nation's next generation. Encouraging educators to pay more attention to the application of character education to students, the school environment is an environment where students can learn about various characters so as not to be influenced by outside cultures that have negative impacts. This research was allocated to MI Roudlotun Nasyi'in Singosari Malang. In this study, the researcher used qualitative research with the type of case study research, the methods used in the research were observation, documentation and interviews. In this study, the researchers found that at MI Roudlotun Nasyi'in the application of the character values of love for the homeland was good, even the teachers already had a special way of implementing character education to students. In addition, various activities are carried out to build the character of love for the homeland of students, for example, scouts, flag ceremonies, commemoration of national holidays and activities inside and outside the school are also carried out. students apply. Keywords: Implementation, Character, Homeland